Obywatelskie kompetencje polityczne a wybrane motywy podejmowania decyzji wyborczych - Alberski, Robert; Plecka, Danuta (Political Preferences, 2015)
Civil political competency and chosen reasons when taking electoral decisions Civil political competency, but especially public trust are the basis of development of the civil society. Level of civil political competency also influence the electoral behaviour. In a research made in the end of 2014 we asked about Polish people civil political competency and about chosen reasons when taking electoral decisions. The group who declares an absence in the election or not taking big care about their electoral decisions and also have lack of skills to determine on which place on the left-right line they are, give evidence of a very low level of civil political competencies. Less important for them are programs and future plans presented by the politicians and political parties and also how they realize them (or not). When taking an electoral decision on the local level, this group take a lesser degree of care then other voters about the local elections candidates (for mayors, council member etc.) memberships to the political parties. Key words: political competences, electoral behavior, electoral decisions, political parties, parliamentary elections, local elections